Missionary activity of Tobolsk-Tyumen diocese in the north of Western Siberia in the 1990s — 2010s - Tatiana Tkacheva; Natalia Kharina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the main directions, forms and methods of missionary activity of the Tobolsk-Tyumen diocese among the indigenous population of the North of Western Siberia in 1990 – 2010. The research was based on publications in the diocesan periodical press, the works of the Tobolsk Theological Seminary, field materials of the authors. The article examines the state of Orthodoxy among the indigenous population by the early 1990s, the specifics of the organization and implementation of the diocesan mission in the territories of the Khanty-Mansi Autonomous Okrug (KhMAO) and Yamalo-Nenets Autonomous Okrug (YANAO). It is shown that in the post-Soviet period, in the conditions of changing relations between the state and the Russian Orthodox Church, the restoration of its missionary activity and the expansion of the Orthodox space in the historically nurtured territories gradually took place. It is concluded that educational, apologetic, informational forms of work were the most common in the missionary activity of the Tobolsk–Tyumen diocese in the North of Western Siberia in 1990 - 2010. The fulfillment of socially significant functions by the diocese contributed to the expansion of the Orthodox presence in the territory. In the 1990s, the missionary activity of the diocese among the indigenous population of the North was limited due to insufficient material and financial situation, lack of personnel and premises for religious rites, parish work. In the 2000s, in the context of establishing stable ties with government administrations of various levels, missionary activity acquired a large-scale character. The article notes that the practice of the Orthodox mission has led to the development of recommendations for the organization of missionary work among the indigenous population, and the specifics of the activities associated with the remoteness and inaccessibility of the northern territories – to the emergence of new forms of missionary expedition.